2020
DOI: 10.21203/rs.3.rs-30634/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actin Reorganization in Hippocampal Neurons May Play Roles in Early Impairment of Learning and Memory in Rats After Propofol Anesthesia

Abstract: Background Perioperative neurocognitive disorder (PND) is a kind of neuronal complication especially observed in elderly patients. The present study was conducted to observe the changes of actin in hippocampus after propofol anesthesia, and to evaluate their roles in consequent learning impairment in both young (3-month-old) and aged (20-month-old) male rats.Methods Double-shuttle box was used to learning evaluation since1, 3, 7 or 14d after anesthesia. Hippocampi were removed after evaluations. F-actin conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…(Platholi et al, 2014) A new preprint reports that propofol anesthesia in rats leads to week-long perturbation of actin structure and learning. (Zhang, Li and Wu, 2020) Those studies have suggested that the anesthetics act directly on actin, but found no evidence for a mechanism. Instead, our results suggest that the anesthetics primarily act in the lipid bilayer part of the membrane by destabilizing lipid nanodomains.…”
Section: Discussionmentioning
confidence: 99%
“…(Platholi et al, 2014) A new preprint reports that propofol anesthesia in rats leads to week-long perturbation of actin structure and learning. (Zhang, Li and Wu, 2020) Those studies have suggested that the anesthetics act directly on actin, but found no evidence for a mechanism. Instead, our results suggest that the anesthetics primarily act in the lipid bilayer part of the membrane by destabilizing lipid nanodomains.…”
Section: Discussionmentioning
confidence: 99%